Librarians View Instruction as Integral to Their Professional Identities - Medaille, Ann (Evidence Based Library and Information Practice, 2011)
Objective – To explore the ways that professional and non-professional library staff experience and relate to their instructional roles. Design – Online survey. Setting – All types of Canadian libraries, including public, school, post-secondary, medical, special, and other libraries. Subjects – A total of 788 library staff persons with instructional responsibilities. Methods – In 2009, the authors constructed a 20-minute anonymous survey that contained questions about the nature of librarians’ instructional work, their preparation for doing instruction, and their experiences as instructors. Subjects were recruited via several electronic mail lists. The authors used SPSS to analyze the quantitative data and NVivo to analyze the qualitative data. Main Results – The study found that the majority of subjects believed instruction to be integral to their professional identities, although some viewed it as an imposition. The nature of instructional work varied greatly, but included short presentations; a series of sessions; semester-length courses; and one-on-one instruction. Subjects prepared for instruction through on-the-job training; reading professional literature; attending workshops and conferences; taking a formal course in instruction; and other methods. On the whole, training helped library staff to feel more prepared for teaching and to embrace instructional work as integral to their professional identities. Study participants derived enjoyment from instruction in the form of satisfaction with facilitating student learning; relationship building; personal development; task variety; and appreciation of the heightened profile of library staff. Subjects also described several barriers to teaching, including administrative, technological, and logistical barriers; client and faculty interactions; and interpersonal challenges such as nervousness or lack of preparation. Finally, subjects described the ways that instruction has changed with the impact of new technologies, increased expectations, and changing pedagogical practices. Conclusion – Library administrators should support the teaching duties of librarians and library staff by helping to provide them with adequate preparation time, resources, emotional support, and training. In addition, formal preparation for instruction should be integrated into professional library training programs, including MLIS programs, to better prepare librarians and other library staff to participate in information literacy instruction.